Alcohol—dose question and the weakest link in a chemical interplay - Piotr Hamala; Karina Wierzbowska-Drabik (Exploration of Cardiology)
The deleterious consequences of alcohol consumption are extensively documented across various dimensions of human health, encompassing somatic disorders such as nervous system impairments, digestive system abnormalities, and circulatory dysfunctions, in addition to socio-psychological aspects. Within the domain of cardiology, a substantial portion of the ongoing scientific discourse centers on elucidating the toxic dose of alcohol. Presented herewith are the findings from a comprehensive review of the latest publications pertinent to this crucial issue.